Precursors to Systemic Sclerosis and Systemic Lupus Erythematosus: From Undifferentiated Connective Tissue Disease to the Development of Identifiable Connective Tissue Diseases - Martin Calderon, Leonardo; Pope, Janet E. (Frontiers in Immunology, 2022)
The pathogenesis of connective tissue diseases (CTDs), such as systemic lupus erythematosus (SLE) and systemic sclerosis (SSc), is characterized by derangements of the innate and adaptive immune system, and inflammatory pathways leading to autoimmunity, chronic cytokine production, and chronic inflammation. The diagnosis of these diseases is based on meeting established criteria with symptoms, signs and autoantibodies. However, there are pre-clinical states where criteria are not fulfilled but biochemical and autoimmune derangements are present. Understanding the underlying processes responsible for disease pathogenesis in pre-clinical states, which place patients at increased risk for the development of established connective tissue diseases, represents an opportunity for early identification and potentially enables timely treatment with the goal of limiting disease progression and improved prognosis. This scoping review describes the role of the innate and adaptive immune responses in the pre-clinical states of undifferentiated CTD at risk for SSc and prescleroderma, the evolution of antibodies from nonspecific to specific antinuclear antibodies prior to SLE development, and the signaling pathways and inflammatory markers of fibroblast, endothelial, and T cell activation underlying immune dysregulation in these pre-clinical states.